218 Cerebral lipiodol embolisation following lymphangiography – a rare neurologi- cal presentation. Issue 6 (27th May 2022) - Batcheller, Lisa; Thaller, Mark; Wright, Benjamin
Abstract : Presentation: A 73-year-old gentleman was admitted for 2 stage oesophagectomy (laparascopic abdominal and open thoracic) which was reported as uneventful. The tumour was subsequently confirmed T2N0M0 therefore cured by the operation. 3 days post operation increasing chest drain output was noted, this became milky with coarse creps on auscultation and this was confirmed later as a chyle leak. Intervention: Interventional radiology performed lymphangiography under local anaesthesia on day 26 post op. Complication: The day after the procedure his GCS dropped with bilateral miotic pupils, increased tone and double incontinence. Initial bloods, arterial blood gas and glucose were normal. Naloxone was given with limited response. His surgical team requested CT head and neurology review. Results: CT head showed patches of high density throughout basal ganglia, cortex and cerebellum but no infarct in keeping with embolization of lipiodol contrast medium. MRI head confirmed maturing ischaemic cortical and subcortical change. Management: The neurological picture showed an encephalopathy with more left sided upper motor neuron signs than on the right. He was managed initially in intensive care with supportive management however prognosis was unclear with no evidence-based treatment. There was also risk of late inflamma- tory reaction analogous to arachnoiditis seen post myelography. Outcome: He subsequently had thoracotomy with clipping/suturing of the left thoracic duct. He was discharged home after three months in hospital. lisabatch1@gmail.com